Services Innovation for Smart City Destinations: The Case of Bandung City - Suwandi, Andreas; Ardhita, Mayadhisa; Setiadi, Raditya Pratama (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2023)
Purpose of the study: Smart City in the city can be seen through technology, people, and financial systems that support city life. This city also strives by creating the Smart Tourism Destination concept which aims to attract and provide tourist needs by combining ICT, culture, and tourism industry in the city of Bandung. Design/methodology: This research is carried out using a descriptive qualitative approach that is useful for testing and developing an understanding of lesser-known phenomena, and is useful for allowing the accumulation of in-depth information about the subject of the study. Data collection uses structured interviews with experts and is obtained through secondary data such as journal articles, reports, organization webpages, and policy documents that are researched to gain a broader perspective on smart city program innovation. Findings: The study shows Bandung effectively utilizes the smart city concept for tourism, highlighting destinations like the Asian-African Museum and Bukit Bintang on the Smart City website and app. However, its technological execution, with 300 flawed applications, remains below expectation. Research limitations/Implications: The research is restricted to a descriptive qualitative approach, which might not provide quantifiable measures of the smart city's success. The research focuses mainly on the tourism aspect of the smart city concept, potentially overlooking other critical facets of the initiative. Novelty/Originality of the study: This study provides a unique insight into the application of the smart city concept specifically for tourism in Bandung, a relatively new endeavour started in 2016. The research bridges the gap between smart city planning and its practical impact on tourism, using Bandung as a case study.